2016
DOI: 10.11648/j.jgo.20160406.13
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Safe Delivery Services Utilization and Associated Factors Among Women of Childbearing Age in Egela Sub-Woreda, Tigray, Northern Ethiopia

Abstract: Abstract:In Ethiopia, the levels of maternal and infant mortality and morbidity are among the highest in the world.Community based studies about safe delivery service utilization are not enough. As per the few studies done, professional assisted delivery is low in the country and particularly in Tigray region where the study was conducted. Community based cross sectional both quantitative and qualitative study were conducted in subworeda Egela, Northern Ethiopia on assessment of safe delivery service utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Compared to previous year's level of ANC service utilization level; it was in an increasing order. In support of this report and recent mini national health survey of Ethiopia 2014, a number of studies from the country revealed a low level of ANC utilization in different health care settings [22,30,31] . The most common factors cited for low level of ANC utilization were low level of awareness and perception towards ANC, low perception level for maternal health, low awareness for pregnancy complication, low level of educational status of women, low level of economic status of women.…”
Section: Male Partner Involvements In Pmtct Of Hiv/aidssupporting
confidence: 56%
See 3 more Smart Citations
“…Compared to previous year's level of ANC service utilization level; it was in an increasing order. In support of this report and recent mini national health survey of Ethiopia 2014, a number of studies from the country revealed a low level of ANC utilization in different health care settings [22,30,31] . The most common factors cited for low level of ANC utilization were low level of awareness and perception towards ANC, low perception level for maternal health, low awareness for pregnancy complication, low level of educational status of women, low level of economic status of women.…”
Section: Male Partner Involvements In Pmtct Of Hiv/aidssupporting
confidence: 56%
“…Moreover, only 7% of the women got the chance to attend PNC [16] . In support of the national health survey of the country, a number of studies from the countries revealed that low level of institutional delivery; ranged from 4.1% to 28.6% [22,[29][30][31] . In contrast to these studies one study revealed 78.8% of the study participants attended institutional delivery in their past delivery [32] .…”
Section: Utilization Of Pmtct Of Hiv Utilization Of Hiv Testing and Cmentioning
confidence: 99%
See 2 more Smart Citations
“…A study conducted in Woldia town and Dodota Woreda, showed that 48.3% and 18.2% gave their last birth at health institutions respectively and in Dodota mothers who were informed about place of delivery were 55 times more likely to deliver at health facilities and women who reside in rural areas were less likely to deliver at health institutions [19,20]. Similarly, the cross sectional study conducted in Tigray region and Munisa Woreda showed that 4.1% 10.3% and 12.3% gave birth at the health facility [21][22][23]. Another study conducted in Sidama zone showed that age and educational status of the mothers and husbands, a frequency of antenatal visit, birth order, and maternal knowledge and prior experience of delivering at a health facility were independent predictors of skilled birth attendance [24].…”
Section: Introductionmentioning
confidence: 93%